1998
DOI: 10.1097/00006250-199811000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Low Birth Weight Infants Among Black and White Parents

Abstract: Objective: To determine whether racial differences in risk of low birth weight infants among black and white parents can be attributed to differences in demographic, behavioral, medical, and socioeconomic factors.Methods: We analyzed 203,815 singleton births from the 1992 California birth certificate data set for the risk of very low birth weight (500 -1499 g) and moderately low birth weight (1500 -2499 g) infants. Additional study variables included maternal (race, age, education, marital status, parity, obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…In addition to low gestational age and birth weight, the striking association of candidemia with race is reemphasized in this study. Although this association may be related to the higher incidence of prematurity among black infants (14), our findings further emphasize the need to identify preventable risk factors and the need to implement preventive measures, such as azole prophylaxis, for this high-risk group (17).…”
Section: Discussionmentioning
confidence: 68%
“…In addition to low gestational age and birth weight, the striking association of candidemia with race is reemphasized in this study. Although this association may be related to the higher incidence of prematurity among black infants (14), our findings further emphasize the need to identify preventable risk factors and the need to implement preventive measures, such as azole prophylaxis, for this high-risk group (17).…”
Section: Discussionmentioning
confidence: 68%
“…[1][2][3] In the USA, several studies have shown that the proportion of low birthweight (<2500 g) is elevated in Black population. [4][5][6][7] Similar findings are seen in the UK in infants of South-Asian, BlackCaribbean and Black-African descent compared with UKborn white mothers. 8 Also, in the Netherlands, studies have shown differences in birthweight and the proportion of low birthweight between the non-Dutch and Dutch populations.…”
Section: Introductionmentioning
confidence: 72%
“…15,18 Infants born to unmarried mothers have been found to have a higher LBW rate 10 ; therefore, maternal marital status was included in the analysis. Adequacy of prenatal care was coded according to standard methods to include the month prenatal care began, number of prenatal visits, and gestation period.…”
Section: Methodsmentioning
confidence: 99%